Foliar Glyphosate Treatment Alters Transcript and Hormone Profiles in Crown Buds of Leafy Spurge and Induces Dwarfed and Bushy Phenotypes throughout its Perennial Lifecycle. Issue 3 (1st November 2017) - Doğramaci, Münevver; Anderson, James V.; Chao, Wun S.; Horvath, David P.; Hernandez, Alvaro G.; Mikel, Mark A.; Foley, Michael E.
Abstract : Leafy spurge ( Euphorbia esula L.) is an invasive weed of North America and its perennial nature attributed to underground adventitious buds (UABs) that undergo seasonal cycles of para‐, endo‐, and ecodormancy. Recommended rates of glyphosate (∼1 kg ha –1 ) destroy aboveground shoots but plants still regenerate vegetatively; therefore, it is considered glyphosate‐tolerant. However, foliar application of glyphosate at higher rates (2.2–6.7 kg ha –1 ) causes sublethal effects that induce UABs to produce stunted, bushy phenotypes. We investigated the effects of glyphosate treatment (±2.24 kg ha –1 ) on vegetative growth, phytohormone, and transcript profiles in UABs under controlled environments during one simulated seasonal cycle. Because shoots derived from UABs of foliar glyphosate‐treated plants produced stunted, bushy phenotypes, we could not directly determine if these UABs transitioned through seasonally induced endo‐ and ecodormancy. However, transcript abundance for leafy spurge dormancy marker genes and principal component analyses suggested that UABs of foliar glyphosate‐treated plants transitioned through endo‐ and ecodormancy. Glyphosate treatment increased shikimate abundance in UABs 7 d after treatment; however, the abundance of shikimate gradually decreased as UABs transitioned through endo‐ and ecodormancy. The dissipation of shikimate over time suggests that glyphosate's target site was no longer affected, but these changes did not reverse the altered phenotypes observed from UABs of foliar glyphosate‐treated leafy spurge. Transcript profiles further indicated that foliar glyphosate treatment significantly affected phytohormone biosynthesis and signaling, particularly auxin transport; gibberellic acid, abscisic acid and jasmonic acid biosynthesis; ethylene responses; and detoxification and cell cycle processes in UABs. These results correlated well with the available phytohormone profiles and altered phenotypes.